2D Mo2CTx Reinforced Polyimide Nanocomposites for Enhancement of Surface Tribological Performance at Elevated Temperatures. Issue 7 (23rd January 2023) - Li, Haonan; Wang, Libo; Li, Liang; Li, Han; Dai, Yahui; Hu, Qianku; Zhou, Aiguo; Liu, Xuqing
Abstract: In order to improve the high‐temperature friction and wear properties of polyimide (PI), Mo2 CTx /PI nanocomposite materials are prepared by using 2D Mo2 CTx MXene as reinforcement. Compared with the properties of pure PI, Mo2 CTx /PI nanocomposites exhibit significant improvement on thermal stability, hardness, and tribological performance. Especially, the addition of Mo2 CTx can reduce friction coefficient and wear rate of PI significantly at different temperatures ranging from room temperature (RT) to 200 °C. The hardness and the thermo‐degradation temperature of composites increase due to the formation of an organic inorganic structure. In addition, this structure helps to form a protective film containing Mo2 CTx nanoflakes, iron oxide, molybdenum oxide, and organic compounds during friction, and improve the tribological properties of PI composite. Abstract : 2D Mo2 CTx nanomaterials are uniformly dispersed in polyimide matrix by a simple hot‐pressing method as reinforcement. The friction coefficient and wear rate of composites are significantly improved at elevated temperatures, which is contributed by the formation of protective and transfer film containing 2D Mo2 CTx nanoflakes, iron oxide, molybdenum oxide, and organic compounds during friction.